Diseminasi Produk Paving Blok Berpori dan Disain Infrastruktur Pejalan Kaki Anak di SLB Kreasi Mandiri - Febriane Paulina Makalew; Steve Wilben Macquarie Supit (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The dissemination product of technology is a continuing research result previously in related to the design prototype of child pedestrian pathway with building block concept. Material developed is the porous paving block. The aim of this paper is to describe and evaluate the dissemination product of technology of the porous paving block and the child pedestrian pathway design. The school area which is used by students and children need safety, comfortable and creative access as well as understanding the use of product porous paving block. The area of school for special needs Kreasi Mandiri does not have access with pavement yet and the school less understanding of suitable material for access of student’s activity. The community service team have constructed the porous paving block with design for children pedestrian as user. The result shows that area of dissemination has been used for pedestrian access and school activity such as sport. Outdoor activity has been the priority for school during pandemic era. Therefore, the dissemination has supported school activity. In the future the community service can be continued by the school with the program in improving school infrastructure through school environment development program.